SISTEM PENGAMBILAN KEPUTUSAN PENERIMAAN KARYAWAN PADA PT. MEGA AUTO CENTRAL FINANCE CABANG MANNA MENGGUNAKAN VISUAL BASIC 6.0 - Maria Aneka Sari; Siswanto Siswanto; Venny Novita Sari (UNIVED Press, 2015)
In a Decision Making System Employee Recruitment happens sometimes difficult to determine qualified employees , especially if the if the employee takes a little and receiving a lot of this is very difficult to determine which ones are good and qualified. Of the various problems that exist , the writer will take a few issues, this is due to limitations in terms of time , cost , effort , and ability to write . The issues that will be examined by the authors include only on the recruitment of employee at Central Auto Finance Branch PT. MEGA Manna.Keyword: Decision Support System, Visual Basic 6.0